IMPROVING LISTENING THROUGH WATCHING TV SERIES AND DEVELOPING SPEAKING THROUGH THE SHADOWING TECHNIQUE - Bakhtiniso Alieva (The Conference Hub, 2025)
This paper examines the integration of two innovative approaches in English language teaching: watching TV series to enhance listening skills and applying the shadowing technique to develop speaking skills. The study emphasizes the importance of authentic audiovisual input and real-time imitation as effective tools for communicative competence. By analyzing theoretical foundations and classroom practices, the research highlights the motivational and pedagogical value of combining entertainment-based learning with focused pronunciation training. Findings demonstrate that TV series provide contextualized and culturally rich input, while shadowing fosters fluency, accuracy, and confidence in oral production. The proposed methodology offers practical recommendations for teachers aiming to balance traditional methods with modern interactive strategies in EFL contexts.
Keywords: listening, speaking, TV series, shadowing technique, communicative competence, methodology.